A 30-year analysis of urolithiasis burden in the North Africa and Middle East region: Findings from the global burden of disease study 2021 - Sina Golestani; Mohammad Taghi Talebian; Ali Golestani; Zeinab Ahadi; Ozra Tabatabaei-Malazy; Ziba Aghsaei Fard; Abdolreza Mohammadi; Bagher Larijani; Seyed Mohammad Kazem Aghamir (PLoS ONE, 2026)
Background Urolithiasis, a prevalent urological disorder, is associated with significant morbidity and economic burden. Despite the Global Burden of Disease (GBD) data, regional specificity for urolithiasis burden in North Africa and Middle East (NAME) remains limited. This study aims to fill this gap by analyzing the burden of urolithiasis in the NAME region from 1990 to 2021. Methods Data from the GBD 2021 study were used to evaluate key health measures, including incidence, prevalence, mortality, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life years (DALYs). Age-standardized rates (ASRs) and absolute numbers were assessed across 21 NAME countries, stratified by sex, age, and sociodemographic index (SDI). Results were presented with 95% uncertainty intervals. Results In 2021, the overall incidence reached 5.3 million (95% uncertainty intervals: 4.2–6.8) cases, compared to 2.0 million (1.6–2.5) in 1990. Prevalence rose from about 76,000 (61,000–96,000) cases in 1990–201,000 (160,000–257,000) in 2021. The number of deaths increased considerably from 142.1 (79.8–194.5) to 394.2 (182.4–509.5), and the DALYs rose from 10,814.0 (7,970.0–13,932.3) to 25,213.3 (17,943.5–33,787.7) from 1990 to 2021. ASRs for all burden measures remained stable and females consistently exhibited lower rates compared to males. There was a positive correlation between SDI and rates of incidence, prevalence, and YLDs; however, deaths, YLLs, and DALYs exhibited no significant correlation with SDI. Conclusion Urolithiasis imposes a growing health and economic burden in the NAME region, particularly among middle-aged populations and high-SDI countries. Targeted interventions and region-specific policies are crucial to address the rising disease burden effectively.